Aspek Hukum Dalam Proyek Konstruksi: Keterlambatan MC-0 Terhadap Stabilitas Cash Flow - Denny Wahyudi Saputra; Busyra Azheri; Muhammad Hasbi (Faculty of Law, Andalas University, 2025)
Delays in the MC-0 (Initial Mutual Check) process in construction projects not only affect cash flow stability, but also have significant legal implications for the parties involved. This study aims to analyze the impact of MC-0 delays on the cash flow stability of construction projects, identify the causal factors, and evaluate the legal consequences based on applicable regulations in Indonesia. This study uses a Systematic Literature Review (SLR) approach by reviewing relevant academic sources, including journals, scientific articles, and laws and regulations. The results of the study indicate that MC-0 delays cause additional costs, such as procurement of materials, labor, and equipment rental, and have the potential to cause contract disputes between service providers and service users. In a legal context, MC-0 delays can lead to default in accordance with the provisions of the Civil Code (KUHPerdata) Article 1239 and Law Number 2 of 2017 concerning Construction Services, which regulates the rights, obligations, and sanctions for the parties in a construction contract. Delays can also violate the principles of good project governance, as stated in Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services. To overcome these impacts, recommended mitigation steps include optimizing communication between parties, increasing the efficiency of contract administration, utilizing project management technology, and providing reserve funds to anticipate potential delays. This finding emphasizes the importance of integrating technical and legal aspects in managing MC-0 delays to ensure smooth implementation of construction projects, cash flow stability, and compliance with applicable regulations.